1999
DOI: 10.1002/stem.170316
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Hematological Effects of the PEGylated Thrombopoietin Peptide Mimetic GW395058 in Rats and Monkeys After Intravenous or Subcutaneous Administration

Abstract: GW395058, a potent PEGylated peptide human thrombopoietin receptor (HuTPOr) agonist in vitro, is being evaluated for the treatment of thrombocytopenia. GW395058 shares no sequence homology with TPO. In this report the pharmacokinetics and hematological effects of GW395058 in rats and monkeys are described. Doses eliciting thrombocytosis in rodents (2 or 10 µg/kg s.c.) produced insufficient plasma concentration data for pharmacokinetic parameter estimate calculations. At higher i.v. doses in rats (500, 1,000 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…It was anticipated that the cytokine/mimetic peptide fusion proteins would induce less immunogenic response than the fused cytokines. Studies showed that the N-terminal PEGylation improved the potency of TMP (de Serres et al 1999), indicating that the attachment of a large molecule to the N-terminus does not prevent the interaction of TMP with its receptor. Therefore, TMP was fused through its amino termini to the SCF by a flexible peptide linker.…”
Section: Discussionmentioning
confidence: 99%
“…It was anticipated that the cytokine/mimetic peptide fusion proteins would induce less immunogenic response than the fused cytokines. Studies showed that the N-terminal PEGylation improved the potency of TMP (de Serres et al 1999), indicating that the attachment of a large molecule to the N-terminus does not prevent the interaction of TMP with its receptor. Therefore, TMP was fused through its amino termini to the SCF by a flexible peptide linker.…”
Section: Discussionmentioning
confidence: 99%
“…The TPO mimetic peptide GW395058 38,39 was synthesized by Genosys Biotechnologies (The Woodlands, TX). Recombinant human EPO and stem cell factor (SCF) were from Boehringer-Mannheim (Mannheim, Germany) and PromoCell (Heidelberg, Germany).…”
Section: Cytokines Reagents and Antibodiesmentioning
confidence: 99%
“…Although a nity of the EPO-mimetic peptide (EMP) was about three logs less than EPO itself (Wrighton et al, 1996), the TPO mimetic peptide (TMP) a nity was remarkably close to that of the native hormone (Cwirla et al, 1997). Injection of 2 mg/kg of a polyethylene glycol modi®ed TMP resulted in doubling of the platelet count, and 10 mg/kg tripled or quadrupled the count (de Serres et al, 1999). The e ects in monkeys were not quite as impressive and a much higher dose was required to double the platelet counts, but the TMP has also been shown to protect animals from severe thrombocytopenia following chemotherapy (Case et al, 2000).…”
Section: Tpo-mimetic Moleculesmentioning
confidence: 99%